Modification of Selected Host-reactive Properties of Endotoxin by Treatment with Sodium Deoxycholate - Tarmina, D. F. (1968)
Endotoxin dissociated into subunits by sodium deoxycholate treatment exhibited diminished capacity to kill chick embryos, protect mice against the lethal effects of infection with Salmonella typhi, evoke hemorrhagic necrosis in skin inoculated with epinephrine, prepare for and provoke the dermal Shwartzman reaction, and induce pyrogenic tolerance. Surfactant-treated material which had been allowed to reaggregate displayed activity equivalent to that of untreated material. These findings were consistent with the working hypothesis that a macromolecular complex of critical size is required in order for endotoxin to elicit its characteristic effects in the host.